Introduction Of An Orthodontic Appliance To Move The Upper First Molars İn Rats - M. Cem Caniklioğlu; Yıldız Kırlıç; Namık Soydan (Galenos Yayinevi, 1999)
The aim of this study is to present an orthodontic appliance which move the upper first molars in rats mesially and to evaluate the results of this appliance with the findings of other researches. 20 Sprague Dawley rats 220±10 gr. in weight and 90±10 days of age were used in this study and NiTi coil springs were inserted between the first upper molar and incisor as the orthodontic appliance. Animals tolerated the experimental procedures well. Following an initial loss, they all regained their original weights. During the experimental period appliance breakage did not occur due to the continuos eruption of upper incisors or to the chewing function. At the end of the experimental period diastema between the first and second molar and food impaction in this area was seen. Histological examination showed that because of food impaction and the wire around the first upper molar pathological changes on alveolar bone occurred.Because of continuos eruption of upper incisors in rats applying the orthodontic appliance to the molars would have some advantages over the other appliances applied to the incisors. Difficulties in inserting the appliance and pathological changes on alveolar bone are two main disadvantages of this appliance.